FISHERY ANALYSIS ON SHORTFIN MAKO Isurus Oxyrinchus, OFF SOUTHEAST AND SOUTH OF BRAZIL (ELASMOBRANCHII: LAMNIDAE) - Costa, Fábio Edir dos Santos; Braga, Francisco Manoel de Souza; de Amorim, Alberto Ferreira; Arfelli, Carlos Alberto (Arquivos de Ciências do Mar, 2018)
The mako shark fisheries by Santos (SP) longliners, operating in the area 18°33' S- 35°51' W, from 1971 to 1990, were studied. The annual catch in dressed weight (without head, gut, gill and fins) fluctuated from 13.3 t, in 1975 to 138.3 t, in 1990. The average weight ranged from 41 kg (1984) to 51.2 kg (1977). The fishing effort has increased from 430 thousand hooks (1972) to 3 million hooks (1990). The CPUE (number per thousand hooks) ranged from 0.6 (1982) to 1.8 (1988). The lowest monthly cumulative catch occurred in February (45 t and 869 fishes) and the highest in November (116 t and 2,643 fishes). The monthly cumulative fishing effort ranged from 1.3 million (February) to 2.7 million (November). The CPUE ranged from 0.4 (January) to 1.1 (September) fish per thousand hooks. From April to November the catches in weight and number were higher, but the mean individual weight decreased. The pectoral-caudal length/dressed weight relationship was: DW = 5.69 10-5 Lc2,86. The highest annual frequencies of pectoral-caudallength werein the classes among 90 and 150 em, but mainly 110 to 130 em classes.